Transformative Pedagogy for Contemporary Education to Strengthen Competencies and Global Learning Readiness - Sarah Elizabeth Anderson (PT. Islamic Research Publisher, 2025)
The rapid evolution of knowledge, technology, and global interconnectivity has necessitated a paradigm shift in contemporary education. This study explores the implementation of transformative pedagogy to enhance students’ competencies and readiness for global learning environments. The primary objective is to investigate how transformative teaching approaches can foster critical thinking, creativity, collaborative skills, and intercultural awareness among learners, thereby preparing them for complex and dynamic global contexts. This study employs a qualitative field research approach involving 350 students and 45 educators from higher education institutions that implement transformative pedagogy. Data were collected through interviews, observations, and documentation to understand teaching practices and student learning experiences. The data were analyzed thematically to identify patterns in instruction and their impact on competency development and global readiness, with validity strengthened through data triangulation. Findings indicate that transformative pedagogy significantly enhances students’ problem-solving abilities, adaptive learning, and intercultural competencies. Active learning strategies, reflective practices, and collaborative projects emerged as key drivers of enhanced engagement and deep learning. Furthermore, students exposed to these pedagogical approaches demonstrated higher self-efficacy, critical thinking skills, and preparedness for international academic and professional contexts compared to peers in conventional learning environments. The study contributes to the academic discourse on educational innovation by providing empirical evidence that transformative pedagogy is an effective approach to strengthening both cognitive and socio-emotional competencies required for global readiness. Implications for policy and practice suggest that institutions should prioritize curriculum redesign, faculty development, and the integration of experiential and culturally responsive learning models. This research lays the foundation for further studies on scalable, sustainable pedagogical transformations that equip learners to meet the challenges of the 21st century.